2021
DOI: 10.5187/jast.2021.e65
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a fall cut on dry matter yield, nutritive value, and stand persistence of alfalfa

Abstract: Competing interestsNo potential conflict of interest relevant to this article was reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…In overall, the forage DMY was observed higher in the second year (2019) for all treatments which might be because of the higher rainfall (1,188 mm) received in 2019 than in 2018 (927mm). No significant yield differences were noted between reduced-lignin alfalfa (RLA) and conventional alfalfa (COA), which was consistent with our previous studies 35,36 where we did not find significant dry matter yield difference between RLA and COA.…”
Section: (A) (B) (C) Fig 3: Effect Of Applied Potassium (A) Varieties...supporting
confidence: 92%
“…In overall, the forage DMY was observed higher in the second year (2019) for all treatments which might be because of the higher rainfall (1,188 mm) received in 2019 than in 2018 (927mm). No significant yield differences were noted between reduced-lignin alfalfa (RLA) and conventional alfalfa (COA), which was consistent with our previous studies 35,36 where we did not find significant dry matter yield difference between RLA and COA.…”
Section: (A) (B) (C) Fig 3: Effect Of Applied Potassium (A) Varieties...supporting
confidence: 92%
“…Despite its multiple benefits, there has been limited progress in yield and production in the United States for decades. However, previous studies have shown that yields of 13–19 Mg ha −1 or more are achievable with proper management practices and favorable growing conditions (Baral et al, 2022; McDonald et al, 2021).…”
Section: Introductionmentioning
confidence: 99%